2021
DOI: 10.6023/a20080384
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Photocatalytic CO2Reduction Based on Two-dimensional Materials

Abstract: In past decades, global warming, sea level rising, and other climate problems caused by greenhouse effect are becoming more and more serious. Considerable efforts have been paid on developing new technology that can effectively reduce the atmospheric level of carbon dioxide (CO 2 ), the most representative one of greenhouse gases. Solar-driven conversion of CO 2 into high value-added hydrocarbon fuels is considered as the most promising approach to alleviate the current energy crisis and the rising CO 2 level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 126 publications
(203 reference statements)
0
1
0
Order By: Relevance
“…Among them, Janus materials have received more and more attention because of their potential excellent photocatalytic properties, [12][13] which contain all the advantages of 2D materials (high specific surface area, short carrier migration distance, tunable electron structure, etc.). [14] Furthermore, due to the intrinsic polarization caused by the structural asymmetry, the generated built-in electric field can effectively suppress the recombination of the carrier. In particular, Ju et al [15] found that the conduction band and valence band are respectively contributed by the Se atomic layer and the S atomic layer in the study of WSSe.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Janus materials have received more and more attention because of their potential excellent photocatalytic properties, [12][13] which contain all the advantages of 2D materials (high specific surface area, short carrier migration distance, tunable electron structure, etc.). [14] Furthermore, due to the intrinsic polarization caused by the structural asymmetry, the generated built-in electric field can effectively suppress the recombination of the carrier. In particular, Ju et al [15] found that the conduction band and valence band are respectively contributed by the Se atomic layer and the S atomic layer in the study of WSSe.…”
Section: Introductionmentioning
confidence: 99%